The role of ubiquitin-dependent segregase p97 (VCP or Cdc48) in chromatin dynamics after DNA double strand breaks - Torrecilla, Ignacio; Oehler, Judith; Ramadan, Kristijan (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2017)
DNA double strand breaks (DSBs) are the most cytotoxic DNA lesions and, if not repaired, lead to chromosomal rearrangement, genomic instability and cell death. Cells have evolved a complex network of DNA repair and signalling molecules which promptly detect and repair DSBs, commonly known as the DNA damage response (DDR). The DDR is orchestrated by various post-translational modifications such as phosphorylation, methylation, ubiquitination or SUMOylation. As DSBs are located in complex chromatin structures, the repair of DSBs is engineered at two levels: (i) at sites of broken DNA and (ii) at chromatin structures that surround DNA lesions. Thus, DNA repair and chromatin remodelling machineries must work together to efficiently repair DSBs. Here, we summarize the current knowledge of the ubiquitin-dependent molecular unfoldase/segregase p97 (VCP in vertebrates and Cdc48 in worms and lower eukaryotes) in DSB repair. We identify p97 as an essential factor that regulates DSB repair. p97-dependent extraction of ubiquitinated substrates mediates spatio-temporal protein turnover at and around the sites of DSBs, thus orchestrating chromatin remodelling and DSB repair. As p97 is a druggable target, p97 inhibition in the context of DDR has great potential for cancer therapy, as shown for other DDR components such as PARP, ATR and CHK1.This article is part of the themed issue 'Chromatin modifiers and remodellers in DNA repair and signalling'.